Implémentation de la méthode asymptotique numérique dans CAST3M - Daridon, Loïc; Charras, Thierry (European Journal of Computational Mechanics, 2004)
This paper deals with the implementation of the numerical asymptotic method in an industrial finite element code. This code is CAST3M, developed by the C.E.A. We present the implementation of the geometrically non linear elasticity case. We propose two approaches: firstly an updated Lagrangian one in which displacements are referred to the updated configuration and secondly a classical Lagrangian one in which displacements are referred to the undeformed configuration. Then, we present a numerical application with a large number of degrees of freedom, 180 000 dof and 300 000 dof. With this application, we can evaluate various calculation times and the efficiency of the method in an industrial frame work.